2010
DOI: 10.1111/j.1469-7580.2010.01275.x
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the development of the visual cortex: implications for plasticity and repair

Abstract: The visual cortex comprises over 50 areas in the human, each with a specified role and distinct physiology, connectivity and cellular morphology. How these individual areas emerge during development still remains something of a mystery and, although much attention has been paid to the initial stages of the development of the visual cortex, especially its lamination, very little is known about the mechanisms responsible for the arealization and functional organization of this region of the brain. In recent year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 205 publications
1
33
0
Order By: Relevance
“…In mammals, although most tissue morphogenesis is completed by birth, it has already been found that this is not the case in the CNS. Both the brain and eye continue to adapt after birth, with significant remodeling of new synaptic connections (16). Our data suggest that this postnatal plasticity might be sufficiently versatile to also allow for reversal of abnormal tissue modeling if the underlying molecular defect is corrected.…”
Section: Resultsmentioning
confidence: 82%
“…In mammals, although most tissue morphogenesis is completed by birth, it has already been found that this is not the case in the CNS. Both the brain and eye continue to adapt after birth, with significant remodeling of new synaptic connections (16). Our data suggest that this postnatal plasticity might be sufficiently versatile to also allow for reversal of abnormal tissue modeling if the underlying molecular defect is corrected.…”
Section: Resultsmentioning
confidence: 82%
“…Injury to the cortex and to subcortical white matter tracts leads to conditions such as cerebral palsy that can involve functional reorganization of cortical areas and projections. James Bourne has described how multiple cortical visual areas develop in the primate brain (Bourne & Rosa, 2006;Burman et al 2007;Bourne, 2010 in this issue) and has shown that focal lesions in the immature brain lead to reorganization of the cortex in different ways to lesions in the adult brain, an issue that has been addressed in various model systems (Huffman et al 1999). Similarly, Janet Eyre and colleagues and Martin Staudt and colleagues have used a battery of techniques, including MRI and neurophysiological recordings in human subjects, to investigate different types of reorganization of the sensorimotor cortex and corticospinal tract in response to developmental lesions as compared with the effects of lesions in the adult (Basu et al 2010;Eyre et al 2007;Walther et al 2009;Staudt, 2010 in this issue).…”
Section: The Impact Of Imaging Techniques In Mapping Human Brain Devementioning
confidence: 99%
“…High salt intake in weanling DS rats modified cataract formation in association with hypertension [6]. In mammals, although most tissue morphogenesis is completed by birth, it has been found that the eye continues to adapt after birth [7]. Therefore, the effects on the eye of the developing organism observed with direct high salt intake might give a hint on how maternal diet could play an important role in early development during pregnancy.…”
Section: Introductionmentioning
confidence: 99%